Standing still is not an option : school children using art for social change - Boske, Christa (New directions in educational leadership (Charlotte, N.C.), 2019)
"This book captures the experiences of children in U.S. public schools and how they utilize artmaking to disrupt injustices they face. These first-time authors, who represent school children, parents, teachers, and community leaders, focus on artmaking for social change. Their first-tellings provide thought-provoking insights regarding the impact of artmaking on their capacity to promote social justice-oriented work in K-12 school communities. As the U.S. continues to experience significant demographic shifts, including increases of homeless children, children identified with learning differences, thousands of refugees and immigrants, children living in poverty, children in foster care, and increasing numbers of Children of Color, those who work in schools will need to know how to address disparities facing these underserved communities. These U.S. demographic shifts and issues facing underserved populations provide opportunities for children, teachers, families, and school leaders to deepen their understanding regarding their experiences within their communities and K-12 schools as well as ways to interrupt oppressive practices and policies they face every day through art as social action. Authors call upon decision-makers who serve children from disenfranchised populations to utilize artmaking to create equal access for children to explore social justice, equity, reflective practices, and promote authentic social action and change through artmaking. Authors reflect on this artmaking process as a catalyst for increasing consciousness, creating imaginative possibilities, and facilitating meaningful change in schools. Authors urge readers to create equal access art spaces to build bridges among schools, families, and communities. Together, they contend that artmaking promotes courageous conversations and encourages the exploration of what it means to live this significant work"--